Rates of Depression, Anxiety, and Stress Among First-Year University Students from Jeddah, Saudi Arabia, During the Year 2020 - Alfakeh, Sulhi A. (Journal of King Abdulaziz University: Medical Sciences, 2023)
Introduction: Psychological distress is a major health concern among students, first-year university students in particular. Depression and anxiety are serious disorders that impair daily functioning. This study aimed to assess the frequency of depression, anxiety, and stress among first-year university students in Jeddah, Saudi Arabia. Methods: A descriptive cross-sectional study was conducted on 929 first-year students from a public university in Jeddah, Saudi Arabia. The data were gathered through an anonymous, self-reported questionnaire sent to all first-year students. The questionnaire comprised three sections: sociodemographic data, the Depression Anxiety Stress Scale-21 (DASS-21), questions on suicidality risk, and previous professional consultations for mental health issues. Data analysis was performed using IBM SPSS version 23. Results: The overall prevalence of symptoms of depression, anxiety, and stress indicators based on the DASS-21 scale was 76%, 69.5%, and 67.4% (n = 929), respectively. The levels of anxiety and stress were significantly higher in women students. Moreover, lack of exercise was significantly linked to increased symptoms of depression, anxiety, and stress. Conclusion: A substantial proportion of first-year university students from Jeddah, Saudi Arabia, experienced symptoms of stress, anxiety, and depression. Lack of exercise is a predictor of stress, anxiety, and depression.